A mechanism for bacterial transformation of dimethylsulfide to dimethylsulfoxide: a missing link in the marine organic sulfur cycle. (27th June 2016) - Lidbury, Ian; Kröber, Eileen; Zhang, Zhidong; Zhu, Yijun; Murrell, J. Colin; Chen, Yin; Schäfer, Hendrik
Summary: The volatile organosulfur compound, dimethylsulfide (DMS), plays an important role in climate regulation and global sulfur biogeochemical cycles. Microbial oxidation of DMS to dimethylsulfoxide (DMSO) represents a major sink of DMS in surface seawater, yet the underlying molecular mechanisms and key microbial taxa involved are not known. Here, we reveal that Ruegeria pomeroyi, a model marine heterotrophic bacterium, can oxidize DMS to DMSO using trimethylamine monooxygenase (Tmm). Purified Tmm oxidizes DMS to DMSO at a 1:1 ratio. Mutagenesis of the tmm gene in R. pomeroyi completely abolished DMS oxidation and subsequent DMSO formation. Expression of Tmm and DMS oxidation in R. pomeroyi is methylamine‐dependent and regulated at the post‐transcriptional level. Considering that Tmm is present in approximately 20% of bacterial cells inhabiting marine surface waters, particularly the marine Roseobacter clade and the SAR11 clade, our observations contribute to a mechanistic understanding of biological DMSO production in surface seawater.